2021
DOI: 10.2196/23105
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Compare Provaccine and Antivaccine Discourse Among the Public on Social Media: Algorithm Development Study

Abstract: Background Despite numerous counteracting efforts, antivaccine content linked to delays and refusals to vaccinate has grown persistently on social media, while only a few provaccine campaigns have succeeded in engaging with or persuading the public to accept immunization. Many prior studies have associated the diversity of topics discussed by antivaccine advocates with the public’s higher engagement with such content. Nonetheless, a comprehensive comparison of discursive topics in pro- and antivacc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 71 publications
(140 reference statements)
2
29
0
Order By: Relevance
“…Even on a platform where vaccine misinformation represents a small fraction of the content, algorithmic biases can propagate this misinformation (Shin and Valente 2020) through the presence of "filter bubbles" that expose users only to ideas that they already agree with (Jamison et al 2020). The persuasive influence of these misinformation narratives (Argyris et al 2020), combined with the affordances created by digital technologies to spread information widely (e.g., through bots; Wawrzuta et al 2021), creates the conditions for the massive reach of misinformation on social media.…”
Section: Legitimacy Theorymentioning
confidence: 99%
“…Even on a platform where vaccine misinformation represents a small fraction of the content, algorithmic biases can propagate this misinformation (Shin and Valente 2020) through the presence of "filter bubbles" that expose users only to ideas that they already agree with (Jamison et al 2020). The persuasive influence of these misinformation narratives (Argyris et al 2020), combined with the affordances created by digital technologies to spread information widely (e.g., through bots; Wawrzuta et al 2021), creates the conditions for the massive reach of misinformation on social media.…”
Section: Legitimacy Theorymentioning
confidence: 99%
“…They showed that it was possible to use information about the users that people follow online to help predict their opinions. Finally, other studies also complement sentiment or stance analysis with topic modeling (TM) to automatically identify important topics related to vaccine hesitancy from social media's contents (Argyris et al, 2021;Cotfas et al, 2021;Jiang et al, 2021;Karami et al, 2021;Ma et al 2021;Sear et al, 2020;Tomaszewski et al, 2021). Ma et al (2021) used 3,403,166 tweets collected in a 3-month period (January 2021 to March 2021) to compare two different topic models (Top2Vec and LDA) and identify topics related to vaccine hesitancy in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…As the importance of understanding and tackling COVID-19 vaccination hesitancy grew, increasing efforts have been made to analyse vaccine narratives and discourses, dissemination of false claims and anti-vaccine groups on social media, resulting in the construction of a number of COVID-19 vaccine-focused datasets, without [11,12] or with annotations about veracity (e.g., true or false information) [13], sentiment (e.g., positive, negative or neutral) [14], stance (e.g., pro-or anti-vaccine) [15,16] or topic category (e.g., vaccine development or side effects) [4,17]. The datasets, consequently, can be used to facilitate the research on COVID-19 vaccine-related online information from different aspects, including fact-checking, sentiment analysis, stance detection, and topic analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Topics or themes discussed in the vaccine-related narratives and online debates are an essential dimension. State-of-the-art methods for automatic topic analysis fall typically under one of these categories: topic modelling [18][19][20][21], clustering [11,12,16,22], and inductive analysis [4,17]. Topic modelling, represented by Latent Dirichlet Allocation (LDA) [23], is the most commonly used approach at present [18][19][20][21].…”
Section: Related Workmentioning
confidence: 99%